Reflecting on India's Development Employment, Skill and Health (Springer Singapore, 2018)
The book assesses the development experience by reflecting on a number of aspects, such as growth in relation to employment, regional imbalances and rural-urban distribution. Further, it examines educational attainment and human capital formation issues in the context of the skill shortages the country is facing, and analyses social inequality, including gender, and evaluates a number of empowerment strategies. Lastly, it critically assesses the effectiveness of health services by examining case studies of on-going sanitation, family planning and reproductive health programmes. Presenting both quantitative and qualitative approaches, the papers utilise rare databases that are usually not available in the public domain to reflect on the country's development experience. The book revisits many development concerns, particularly inclusiveness aspects, through an in-depth analysis. It covers three major areas related to (a) employment, (b) education and skill and (c) social concerns and issues related to health services. The book will be an important resource not only for researchers but also for policy makers and those involved in capacity development in these areas.